Landasan Ontologis dalam Pengembangan Kurikulum Pendidikan Agama Islam pada Madrasah Ibtidaiyah - Purnasari, Martina; Mustaqorina, Nabella Oktafiana Sari (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
The current moral decadence is a major concern in the field of education, particularly in Islamic Religious Education (PAI) subjects, which are responsible for instilling moral and religious values in students. This study aims to examine the ontological foundations in the development of the PAI curriculum for the Aqidah Akhlak subject at MI Muhammadiyah 01 Cakru Jember. Utilizing a qualitative method with a case study design, this research involves interviews and observations as the primary data collection techniques, supported by literature reviews. The findings indicate that a curriculum developed based on ontological foundations can serve as an effective reference for educators in implementing Aqidah Akhlak teaching. Key findings include the positive impact of a well-planned curriculum on personal changes in students and the broader community. The implications of this study emphasize the importance of continuous evaluation and monitoring to ensure the curriculum remains on track and supports the development of students' strong and integral character.